A minimum dilution scenario for supernovae and consequences for extremely metal-poor stars - Magg, Mattis; Nordlander, Thomas; Glover, Simon; Hansen, Camilla Juul; Ishigaki, Miho; Heger, Alexander; Klessen, Ralf S.; Kobayashi, Chiaki; Nomoto, Ken’ichi (Monthly notices of the Royal Astronomical Society, 2020)
To date no metal-free stars have been identified by direct observations. The most common method of constraining their properties is searching the spectra of the most metal-poor stars for the chemical elements created in the first stars and their supernova (SN). In this approach, modelled SN yields are compared to the observed abundance patterns in extremely metal-poor stars. The method typically only uses the abundance ratios, i.e. the yields are diluted to the observed level. Following the usual assumption of spherical symmetry we compute a simple lower limit of the mass an SN can mix with and find that it is consistent with all published simulations of early chemical enrichment in the interstellar medium. For three different cases, we demonstrate that this dilution limit can change the conclusions from the abundance fitting. There is a large discrepancy between the dilution found in simulations of SN explosions in minihaloes and the dilution assumed in many abundance fits. Limiting the dilution can significantly alter the likelihood of which supernovae are possible progenitors of observed CEMP-no stars. In particular, some of the faint, very low yield SNe, which have been suggested as models for the abundance pattern of SMSS0313−6708, cannot explain the measured metal abundances, as their predicted metal yields are too small by two orders of magnitude. Altogether, the new dilution model presented here emphasizes the need to better understand the mixing and dilution behaviour of aspherical SNe.